PRE-GESTATIONAL DIABETES: PREGNANT WOMEN'S EXPERIENCE WITH DISEASE CONTROL - Aliny de Lima Santos; Elen Ferraz Teston; Hellen Pollyanna Mantelo Cecilio; Deise Serafim; Sonia Silva Marcon (Universidade Federal do Paraná, 2014)
A descriptive qualitative study, carried out in order to know how pregnant women with pre-existing diabetes deal with the illness. The informants were five women in a high risk prenatal clinic of a University Hospital. The data were collected in June and July 2010, through semi-structured interviews that were recorded, transcribed and analyzed for thematic content, conducted during clinic and prenatal consultations. Two categories emerged: changes encouraged by family members after pregnancy and recognizing the importance of professional monitoring and its guidelines, which show the implementation of significant changes in self-care, with pregnancy and professional guidelines cited as motivating factors. This shows that pregnancy, besides being a landmark in women's lives, also acts as a modifying factor in perception and self-care.